[18F]6‐fluoro‐3, 4‐dihydroxy‐ l‐phenylalanine – recent modern syntheses for an elusive radiotracer. (16th April 2015) - Edwards, Richard; Wirth, Thomas
Abstract [18F]6‐fluoro‐3, 4‐dihydroxy‐ l‐phenylalanine ([18F]F‐DOPA) has been known to be a useful radiotracer for over 30 years. Its widespread clinical use has been hampered by the lack of a robust, high yielding synthesis. This review summarises new developments in radiochemistry that are providing solutions to long standing problems involved in the synthesis of this important but elusive radiotracer. Considerable advances in nucleophilic synthesis have been achieved by optimising multistep strategies and using both hypervalent iodine chemistry and transition metal‐mediated fluorinations allowing for the production of high specific activity [18F]F‐DOPA.